Strategi kreatif Erigo dalam produksi konten audiovisual di TikTok - Tanjung, Sumekar; Azrial, Muhammad Ghozi (Program Studi Ilmu Komunikasi UII, 2026)
The massive growth in TikTok users has made audiovisual content a key tool in building consumer trust. This study aims to analyze the creative strategies of the @erigo.store account in producing audiovisual content and to identify the factors that influence this creative process. This study employs a case study approach. Data were collected through in-depth interviews with Erigo’s creative team and participatory observation of their content production patterns. The findings reveal that Erigo’s creative strategy is implemented through four systematic phases: preparation, incubation, illumination, and evaluation. The production process is strictly executed through pre-production, production, and post-production stages to ensure consistent content quality. Theoretically, this research's implications contribute to the study of creative communication management within the new media ecosystem, particularly regarding the adaptation of traditional production workflows to dynamic short-form video formats. Practically, the results of this research provide a model for creative industry practitioners and other fashion brands to integrate structured production management with the flexibility of digital trends to optimize brand engagement.